Enhancement of Family-Centred Care Is Associated with a Reduction in Postmenstrual Age at Discharge in Preterm Infants - Rahel Schuler; Carola Eiben; Markus Waitz; Bernd A. Neubauer; Andreas Hahn; Walter A. Mihatsch (MDPI AG, 2024)
Background/Objectives: Long hospitalisation has been recognized as an independent risk factor for poor neurodevelopmental outcomes of preterm infants. Systematic training and early inclusion of parents in their preterm infant's care is a strategy to shorten the length of hospital stay. We implemented an enhanced stepwise family-centred care program and assessed its effects on postmenstrual age (PMA) at discharge and parental satisfaction. Methods: This prospective single-centre longitudinal cohort study was carried out in a German level III neonatal unit from October 2020 to May 2023. Five consecutive 6-month cohorts (1 baseline and 4 intervention cohorts, 169 infants and their caregivers) were analysed. Results: Mean PMA at discharge did not change in the total cohort but declined significantly in patients without neonatal morbidities from baseline to cohort 4 (37.2 ± 1.4 to 36.1 ± 1.6 weeks; p = 0.036). Concomitantly, discharge with tube feeding raised from 2.4% to 74.1% (p < 0.001) and discharge with home monitoring raised from 9.8% to 74.1% (p < 0.001), while unplanned readmissions remained unchanged (p = 0.44). Parental satisfaction with time point of discharge increased non-significantly from baseline to cohort 4 (75.8% vs. 95.7%; Chi2 0.22). Conclusions: Discharge of preterm infants at a significantly lower PMA is feasible through enhancement of family-centred care and is very well accepted by parents.